d/dx (sin^3 x) = d/dx (sinx sinx sinx)

2 answers

use the chain rule
y = sin^3x
y' = 3 sin^2x cosx
d/dx (sinx sinx sinx)
=sin x d/dx(sin x sin x) + (sin x sin x) d/dx(sin x)
= sin x d/dx(sin x sin x) + (sin x sin x) cos x
= sin x[2sin x cos x] + sin^2 x cos x
= 2 sin^2 x cos x + sin^2 x cos x
= 3 sin^2 x cos x
which we knew anyway
Similar Questions
  1. Prove the following:[1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)]
    1. answers icon 3 answers
    1. answers icon 3 answers
  2. Simplify sin x cos^2x-sinxHere's my book's explanation which I don't totally follow sin x cos^2x-sinx=sinx(cos^2x-1)
    1. answers icon 1 answer
  3. Hello! Can someone please check and see if I did this right? Thanks! :)Directions: Find the exact solutions of the equation in
    1. answers icon 1 answer
more similar questions